Aportes a la Epidemiología del asma infantil - Marco, Leandro Nicolas (2014)
The project is located in Concepcion del Uruguay, (2005-2010). Objectives: To determine prevalence and incidence of asthma between 6 and 11 years old, describe risk factors, study plants, pollen, fungi and mites. Design: Cross-sectional and follow-up cohort for 5 years. ISAAC survey was applied. The prevalence and incidence found is high. The risk factors include passive smoking, and history of hyperreactivity and wheezing. No significant differences between the sexes, nor by the presence of pets or family history of allergy or asthma. IgE tends to decrease between 8 and 11 years of age, more pronounced in the control group. The main triggers are hyperventilation, climate changes and smoke snuff. The density of mites is high. Among the fungi predominate Cladosporium, Alternaria and Penicillium. 75% of urban trees is allergenic and add grass and ragweed. In spring, high density of Fraxinus is detected, moderate for Poaceae, Myrtaceae, Celtis and Cupresseae. In autumn are infantilmoderate levels to Artemisia, Asteraceae, Ambrosia and Chenopodium. 38% of children with allergic rhinitis and / or asthma showed pollinosis in early autumn and spring. As a preventive strategy should be increased environmental care and secondary prevention in children aged 6 years who have these factors.